The support of Mexico and Cuba to the Basque football team and the Spanish Republic during the Civil War - André Gounot (Universidad Politécnica de Madrid, 2024)
The Euzkadi team was created in the context of the Spanish Civil War following a call from the lehendakari (Basque president) José Antonio Aguirre. Apart from promoting Republican Spain and Basque national culture, its main mission was to raise funds for humanitarian purposes. After playing matches in five European countries and the Soviet Union between April and August 1937, the players decided to continue their tour in South America instead of returning to their rebel-conquered homeland. Their stays in Mexico and Cuba until the summer of 1939 will be analysed under the question of their links with official, public and parallel diplomacy. The main objective is to identify and explain the differences and convergences of interests between governments, national sports institutions, and FIFA.